Community’s Educational Needs During the COVID-19 Pandemic: A Qualitative Study - Mohammad Azadmanesh; Aliasghar Jamalinasab; Atefeh Afshari; Mohammad Reza Soleymani; Habibollah Hosseini; Mahrokh Keshvari (Iranian Journal of Nursing and Midwifery Research)
Background: Due to its unknown nature, multifaceted symptoms, and rapid spread, the coronavirus has become a public health emergency, leading to international concerns. Therefore, this study aims to investigate the community’s educational needs during the COVID-19 pandemic. Materials and Methods: This qualitative research was conducted between 2020 and 2021 using a conventional content analysis approach. The research sample comprised 340 recorded calls from individuals who contacted the emergency hotline of Isfahan University of Medical Sciences during the COVID-19 pandemic to express their concerns and anxieties. Sampling was conducted randomly and purposively until data saturation was achieved. Additionally, Graneheim and Lundman’s approach was utilized for data analysis. Results: After analyzing the interviews, codes related to the reasons for contact were presented in five main categories, including awareness of the nature of the disease, awareness of preventive methods, awareness of diagnostic methods, awareness of treatment methods, and awareness of caring for high-risk groups and 15 subcategories. Conclusions: The results of this study highlighted various concerns regarding the coronavirus disease during pandemic conditions, which can serve as a foundation for appropriate educational and counseling programs based on community needs during future infectious pandemics.